Comorbid Mental Disorders and 6-Month Symptomatic and Functioning Outcomes in Chinese University Students at Clinical High Risk for Psychosis - Shi, Jingyu; Wang, Lu; Yao, Yuhong; Su, Na; Zhan, Chenyu; Mao, Ziyu; Zhao, Xudong (Frontiers in Psychiatry, 2017)
Abstract Background: High rates of non-psychotic psychopathological symptoms have been observed in clinical population at clinical high risk (CHR) for psychosis. These comorbid disorders were influencing the baseline functional level of CHR patients. However, less is known about the comorbid mental disorder in CHR individuals in general adolescent population. This study aimed to investigate the comorbid mental disorder in nonclinical CHR adolescents and the impact on attenuated psychosis symptoms (APS) as well as clinical outcome. Methods: The sample consisted of 32 CHR students, who were screened from 2800 university students. CHR status was evaluated with the Structured Interview of Prodromal Syndromes, comorbid mental disorder diagnoses with the International Neuropsychiatric Interview. Results: In the CHR sample, 46.9% was found at least one non-psychotic comorbid mental disorder. The CHR participants presenting comorbid mental disorder had significantly more severity of APS than those without comorbid mental disorders, and the remission rate at 6-month follow-up is significantly higher in the individuals without comorbid mental disorders at baseline. Conclusion: In the general population sample of individuals at CHR, non-psychotic comorbid mental disorders are common and anxiety disorder is most frequent. Co-presence of anxiety and/or depression related to higher level of attenuated psychotic symptoms and unfavorable clinical outcome at 6-month follow-up. Assessment and intervention in anxiety and depression for nonclinical CHR adolescents are suggested.